Summary of development in expert systems application in western Canada: A tutorial & report on regional initiatives - Gamble, Ken (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
An overview of expert systems will contain an explanation of system structure with a focus on the representation of knowledge. Implications for information retrieval will be discussed as well as systems currently in use. The role of the Alberta Research Council in developing such systems and local developments will be explored.